A Probiotic Mixture Regulates T Cell Balance and Reduces Atopic Dermatitis Symptoms in Mice - Kim, Han Wool; Hong, Rira; Choi, Eun Young; Yu, KeeSun; Kim, Narae; Hyeon, Jin Yi; Cho, Kwang Keun; Choi, In Soon; Yun, Cheol-Heui (Frontiers in Microbiology, 2018)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder with a complex etiology involving the immune response. Recent studies have demonstrated the role of certain probiotics in the treatment and prevention of AD. However, the mechanism by which these probiotics regulate the immune system remains unclear. In this study, we examined the immunomodulatory capacity of Duolac ATP, a mixed formulation of probiotics, both in vitro and in vivo. Results showed that the expression of programmed death-ligand 1(PD-L1) was significantly upregulated on bone marrow-derived dendritic cells (BMDCs) treated with Duolac ATP. Furthermore, the anti-inflammatory cytokines IL-10 and TGF-beta were both upregulated when BMDCs were treated with Duolac ATP. The percentage of proliferated regulatory T-cells (Tregs) was enhanced when CD4+ T-cells were co-cultured with Duolac ATP-treated BMDCs on plates coated with anti-CD3/CD28 antibodies. Intriguingly, IL-10 secretion from CD4+T-cells was also observed. The AD symptoms, histologic scores, and serum IgE levels in AD mice were significantly decreased after oral treatment with Duolac ATP. Moreover, the Th1-mediated response in AD-induced mice treated with oral Duolac ATP showed upregulation of IL-2 and IFN-gamma as well as of downstream signaling molecules T-bet, STAT-1, and STAT-4. Conversely, Duolac ATP suppressed Th2 and Th17 responses in AD-like mice, as evidenced by the downregulation of GATA-3, c-maf, IL-4, IL-5, and IL-17. Additionally, Duolac ATP increased the number of Tregs found at Peyer's patches (PP) in treated AD mice. These results suggest that Duolac ATP modulates DCs to initiate both Th1 and Treg responses in AD mice. Thus, Duolac ATP represents a potential preventative agent against AD and could serve as an effective immunomodulator in AD patients.